Management of fracture Clavicle by Plate and screw Fixation (Journal of Surgical Sciences, 2019)
Purpose: To evaluate radiological & clinical outcome of operative treatment of fractures clavicle Methods: From July 2008 to June 201 1 we performed ORIF on 1 2 adult patients, 9 men and 3 women, aged 20-48yrs with displaced midshaft and distal clavicle fractures at Narayanganj General Hospital, Aysha Memorial Hospital & other private Hospital of Dhaka. Result:AII 1 2 of the fractures healed within 9 weeks with the majority radiographically healed by 6 weeks. There were no malunion. There were no neurovascular complications and only one minor superficial infection treated with a 1 0 day course of oral antibiotics and local wound care. There was no evidence of hardware failure. All patients had returned to their previous activity level at approximately four months follow-up with full range-ofmotion and strength in ·the affected extremity. Conclusion: we believe that ORIF of displaced midshaft clavicle fractures is a safe procedure with excellent clinical outcomes. In the near future we plan to report function of this group using a standardized assessment metric with a minimum two year followup. The orthopedic surgeon should not be tempted to treat a fracture of the clavicle by open reduction merely because .the patient or family objects to a bony prominence at the fracture.Journal of Surgical Sciences (2012) Vol. 16 (2) : 80-85